Numerical modelling of flax short fibre reinforced and flax fibre fabric reinforced polymer composites. (15th March 2016) - Sliseris, Janis; Yan, Libo; Kasal, Bohumil
Abstract: The ever-increasing demand of flax short fibre-reinforced and flax fibre fabric-reinforced polymer composites in various engineering applications calls for accurate predictions of their mechanical behaviors. In this study, numerical methods to generate and simulate mechanical properties of flax short fibre-reinforced and flax fibre fabric-reinforced polymer composites are proposed. The microstructures of short flax fibres with different fibre length-to-diameter ratios are generated by algorithm taking fiber defects (e.g. kink band) and fiber bundles into account. Bidirectional flax fabric is generated and discretized by tetrahedron 4-node finite elements. A brittle material law for fibre defects and interfacial zones of fibre bundles is proposed. Flax short fibre/polypropylene and flax fabric/epoxy composites are modeled by a non-linear plasticity model considering an isotropic hardening law and non-local continuum damage mechanics. The numerical modelling results are compared with the experimental results of these composites. This study shows that the simulation can capture the main damage mechanisms of the composites such as fibre breakage initiated at the fiber defects, damage of polymer matrix and the fibre debonding at fibre/matrix interface accurately. In addition, the simulation results exhibit good agreements with the experimental results in the aspects of elastic properties and nonlinear tensile stress-strain behavior of the short fibre and fibre fabric reinforced polymer composites.